Perlindungan Hak Masyarakat Hukum Adat dalam Pengelolaan Hutan - Syofiarti, Syofiarti; Fatimah, Titin; Aini, Nur (Faculty of Law, Andalas University, 2023)
Forests are one of the valuable assets owned by the Indonesian people. Since a long time ago, forests have been the life support of the surrounding communities, including Customary Law Peoples. In fact, in forest management, the rights of Customary Law Peoples have been determined by the constitution, precisely Article 18B paragraph (2) and Article 33 paragraph (3) of the 1945 NRI Constitution which was later affirmed by derivative rules. Unfortunately, in reality, the use of forests by Indigenous Peoples often contradicts government policies which have implications for the emergence of forestry disputes involving Indigenous Peoples. This study aims to analyze regulations on the rights of Customary Law Peoples (MHA) in managing forests, find factors that trigger the birth of disputes and offer a pattern of protection of MHA rights in forest management. Empirical juridical approach with analytical destriptive nature is the method chosen by the author to examine the problems in this study. The data used consists of two types, namely primary data and secondary data. Then, the collected data will be analyzed qualitatively. The location of this research is focused in West Sumatra Province, precisely in the Mentawai Islands and Nagari Malalo. The results of this study prove that MHA's forest management rights protection arrangements already exist, but have not been able to guarantee MHA's rights protection. This then also became one of the factors triggering the dispute. Therefore, to answer this problem, a pattern of protection is needed by strengthening and consistency in regulating MHA rights in forest management and simplifying the mechanism for recognition of MHA customary forests by the government. It is hoped that the pattern offered can create certainty and legal order in order to achieve legal justice for MHA for forest management.